Kinetic Measurements for Photodecomposition of Bilirubin - Badaruddin Ahmad, Hafiz; Ahmad, Saghir; Aslam Shad, Muhammad; Hussain, Mazhar (Asian Journal of Chemistry, 2013)
In present studies, chloroform solution of bilirubin was exposed to direct sunlight, diffused sunlight, ultraviolet, white, tungsten, blue, green and red lights to observe the degradation process. Multiple wavelength scans ranging from 200-800 nm were obtained after appropriate intervals of time for degradation of bilirubin in all the mentioned lights. It has been observed that the degradation process obeys first order reaction rate. Rates of reactions for different lights are calculated by plotting graph between ln (At-A¥) versus time. Half lives for the photodecomposition of bilirubin were also calculated. A new kinetic model for the rate determination of decomposition reaction is proposed which fits the experimental data in excellent way giving correlation coefficients up to 0.999. Appearance of peaks at other wavelengths in multiple scan indicate the formation of intermediates before complete degradation.